Towards a Robustness Assessment Methodology for IoT Systems - Jesus, Bruno; Leite, Glauber; Antunes, Nuno (Anais do Workshop on Validation and Verification of Future Cyber-physical Systems (WAFERS); 2021: Anais do II Workshop on Validation and Verification of Future Cyber-physical Systems, 2021)
Internet-based systems are definitely present in people's daily lives, helping to perform various activities and providing greater comfort and ease in communication. In this context of diversification, every day more devices have access to the network, further increasing the reach and distribution of information around the world, including IoT systems, which are critical in some scenarios. In this context, this paper proposes a methodology to assess the robustness of an IoT System, based on a scenario with an automated system for growing vegetables that was initially designed for residential scale but which can be adapted for industrial scale. We use components commonly used in IoT systems, which facilitates scalability and allows for robustness testing. We aim to test the robustness of these components by creating a test case methodology and performing many test cases for each endpoint. From this analysis we intend to improve security mechanisms in IoT environments with characteristics similar to the proposed scenario. Finally, we will check the behavior of the software components in the presence of errors and problems with the data sent.